(untitled) (Bangladesh Journal of Child Health, 2024)
Background: Pancreatitis is an inflammatory condition of the pancreas, which might extend to local and distant extra-pancreatic tissues. It can be acute, acute recurrent or may be chronic. The diagnosis of different types of pancreatitis is based on a combination of clinical signs and symptoms, laboratory investigations and imaging techniques. Objective: To describe and find out the association of the laboratory and imaging profiles of different variety of pancreatitis in children. Methods: It was a an observational study conducted at the department of Paediatric Gastroenterology and Nutrition of Bangabandhu Sheikh Mujib Medical University from July 2018 through June 2020. A total of 48 cases were included in this study. The diagnosis of acute, acute recurrent and chronic pancreatitis was based on diagnostic criteria made by INSPPIRE group. Clinical characteristics, hematological, biochemical and imaging profile of the different variety of pancreatitis and their hospital outcome were observed. Result: Among 48 cases, acute recurrent pancreatitis were 56.3%. Mean age of the patients at presentation was 10.3 years. Laboratory tests showed serum calcium and C-reactive protein was significantly altered among acute, acute recurrent and chronic pancreatitis with characteristic imaging findings. Among imaging modalities, abdominal ultrasonogram showed swollen pancreas (58.3%) was significantly common in acute recurrent pancreatitis than chronic pancreatitis, whereas shrunken pancreas (28%) was significantly common findings in chronic pancreatitis. In addition to ultrasonogram, MRCP aided diagnosis of chronic pancreatitis. Complications developed in 25% of acute pancreatitis cases, which included hypocalcemia (58.3%), ascites (86.7%), pleural effusion (66.7%), pseudocyst (33.3%) and pancreatic necrosis (25%). Hospital stay was significantly prolonged in acute pancreatitis cases, when compared to other types of pancreatitis . Conclusion: Low calcium level and high CRP level were found in acute pancreatitis than in acute recurrent and chronic pancreatitis. Swollen pancreas with beaded and tortuous pancreatic ducts were found in case of chronic pancreatitis. Bangladesh J Child Health 2023; Vol 47 (2) : 95-102